Analyzing Financial Capital Behavior in the Renewable Energy Sector of Nepal - Yadav, Maheshwar Prasad (International Research Journal of MMC, 2023)
The paper aims at analyzing financial capital behavior in the renewable energy sector of Nepal. The study consists of a descriptive research design based on both primary and secondary data. The necessary primary data were collected through a field survey by using a structured questionnaire on a sample of 118 Nepalese renewable energy enterprises having 264 respondents while the secondary data were collected through the relevant publications from January to March 2016. The collected data were analyzed using simple statistical tools such as tables, mean, rank, and percentage to derive results leading to major findings of the study. The major components of the renewable energy sector comprise biogas, solar and micro-hydro companies ranging from micro to medium enterprises in Nepal. The study concludes that the initial investment appeared to vary with the sectors of enterprises. The major source of financial capital for renewable energy enterprises is their capital. Financial capital is a vital and basic requirement of entrepreneurship in the sector. This study is useful for biogas companies, solar companies, and micro-hydro construction companies to grow their own business by focusing on the financial capital behavior in the renewable energy sector of Nepal. The study can be extended by incorporating other sectors of renewable energy, such as improved cooking stoves, wind technology, and biomass sectors to get greater insight into the results.